Genome-wide methylation profiling and copy number analysis in atypical fibroxanthomas and pleomorphic dermal sarcomas indicate a similar molecular phenotype - Kölsche, Christian; Stichel, Damian; Griewank, Klaus G.; Schrimpf, Daniel; Reuss, David; Bewerunge-Hudler, Melanie; Vokuhl, Christian; Dinjens, Winand N. M.; Petersen, Iver; Mittelbronn, Michel; Cuevas-Bourdier, Adrian; Buslei, Rolf; et al. (Clinical Sarcoma Research, 2019)
Atypical fibroxanthomas (AFX) and pleomorphic dermal sarcomas (PDS) are lesions of the skin with overlapping histologic features and unspecific molecular traits. PDS behaves aggressive compared to AFX. Thus, a precise delineation, although challenging in some instances, is relevant.